2018
DOI: 10.1002/2017ja024664
|View full text |Cite
|
Sign up to set email alerts
|

Generation Mechanism for Interlinked Flux Tubes on the Magnetopause

Abstract: We use a global magnetohydrodynamics simulation to analyze transient magnetic reconnection processes at the magnetopause. The solar wind conditions have been kept constant, and an interplanetary magnetic field with large duskward BY and southward BZ components has been imposed. Five flux transfer events (FTEs) with clear bipolar magnetic field signatures have been observed. We observed a peculiar structure defined as interlinked flux tubes (IFTs) in the first and fourth FTE, which had very different generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…We further discuss the link between a prevailing large IMF B y component in the solar wind and the formation of such structures. Two mechanisms were proposed by Farinas Perez et al (2018) on the basis of simulation and suggest that interlaced flux tubes may form either through resistive tearing instability developing at the subsolar point or through the evolution of a regular FTE into a more complex 3‐D structure. We propose an additional formation mechanism based on the maximum magnetic shear angle model at the magnetopause (Trattner et al, 2007), which can create bifurcated X‐lines at the dayside magnetopause for large IMF B y .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We further discuss the link between a prevailing large IMF B y component in the solar wind and the formation of such structures. Two mechanisms were proposed by Farinas Perez et al (2018) on the basis of simulation and suggest that interlaced flux tubes may form either through resistive tearing instability developing at the subsolar point or through the evolution of a regular FTE into a more complex 3‐D structure. We propose an additional formation mechanism based on the maximum magnetic shear angle model at the magnetopause (Trattner et al, 2007), which can create bifurcated X‐lines at the dayside magnetopause for large IMF B y .…”
Section: Resultsmentioning
confidence: 99%
“…First, the influence of the IMF B y on the occurrence of interlaced flux tubes was investigated through simulation by Cardoso et al (2013) and more recently by Farinas Perez et al (2018). When imposing a strong B y component on the IMF together with a southward B z , they observed the formation of two “interlinked” flux tubes (called IFT) out of five FTE‐type structures generated in the simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common approach in reconnection studies in global MHD simulations is to apply an anomalous resistivity (Komar et al, 2015), and has been found necessary when simulating substorms (Raeder et al, 2001). However, numerous simulations (Raeder, 2006;Cardoso et al, 2013;Perez et al, 2018) have shown that flux ropes can form with numerical resistivity, and anomalous resistivity has no impact on dayside reconnection (Raeder, 2006).…”
Section: Methodology the Gorgon Mhd Codementioning
confidence: 99%
“…Other flux tubes were found to be interlinked with field lines of different topology. Perez et al (2018) further reported a study showing a number of flux ropes spontaneously forming under constant solar wind parameters.…”
Section: Introductionmentioning
confidence: 94%